Pengaruh Metaverse Di Bidang Pendidikan - Irfan Rizky Herlambang; Mohamad Ridho Ramadhan; Rizky Sya Ujiwantanu (Prosiding Seminar Nasional Teknoka, 2023)
As technology develops, sharing has been done to support learning. In the social 5.0 era, there are 3 things that must be utilized, namely: Internet of Things in the world of education (IoT), Virtual/Augmented Reality in the world of education, and the use of Artificial Intelligence (AI). So this research was carried out to find out how important the metaverse is for supporting learning. The results of research using this literature study show that the implementation of Metaverse in the education sector has great potential to support distance learning activities that are more interactive and immersive. In addition, Metaverse can provide scientific laboratory simulations, classroom simulations, or historical environment simulations that allow users to learn and interact in that environment.